Impact of human immunodeficiency virus (HIV) infection on the progression of liver fibrosis in hepatitis C virus infected patients. Issue 7 (1st July 2003) - Mohsen, A H; Easterbrook, P J; Taylor, C; Portmann, B; Kulasegaram, R; Murad, S; Wiselka, M; Norris, S
Abstract : Objectives: To compare the rate of hepatic fibrosis progression in hepatitis C virus (HCV) infected and human immunodeficiency virus (HIV)-HCV coinfected patients, and to identify factors that may influence fibrosis progression. Patients and methods: A total of 153 HCV infected and 55 HCV-HIV coinfected patients were identified from two London hospitals. Eligible patients had known dates of HCV acquisition, were HCV-RNA positive, and had undergone a liver biopsy, which was graded using the Ishak score. Univariate and multivariate logistic regression analyses were used to identify factors associated with fibrosis progression rate and the development of advanced fibrosis (stages 3 and 4). Results: The estimated median fibrosis progression rate was 0.17 units/year (interquartile range (IQR) 0.10–0.25) in HIV-HCV coinfected and 0.13 (IQR 0.07–0.17) in HCV monoinfected patients (p=0.01), equating to an estimated time from HCV infection to cirrhosis of 23 and 32 years, respectively. Older age at infection (p<0.001), HIV positivity (p=0.019), higher alanine aminotransferase (ALT) level (p=0.039), and higher inflammatory activity (p<0.001) on first biopsy were all independently associated with more rapid fibrosis progression. ALT was correlated with histological index ( r =0.35, p<0.001). A CD4 cell count ⩽250×10 6 /l was independently associated with advanced liver fibrosis (odds ratio 5.36 (95% confidence interval 1.26–22.79)) and was also correlated with a higher histological index ( r =−0.42, p=0.002). Conclusion: HIV infection modifies the natural history of HCV by accelerating the rate of fibrosis progression by 1.4 fold, and the development of advanced fibrosis threefold. A low CD4 cell count was independently associated with advanced disease and correlated with higher histological index, which suggests that early antiretroviral therapy may be of benefit in slowing HCV progression in coinfected patients.